Collaborative Governance Process in the Indonesia - Malaysia Border Area in North Kalimantan Province - Aji Primanto; Linda Puspitasari (PT ARRUS Intelektual Indonesia, 2023)
This research aims to analyze and describe the Collaborative Governance process carried out by the Regional Police of North Kalimantan Province conducted by the State Mission in the Field of Border Security between Indonesia and Malaysia. The results of the research indicated that the collaboration process by the North Kalimantan Regional Police with relevant stakeholders in the Republic of Indonesia - Malaysia border area is not optimal. When the North Kalimantan Regional Police carried out a collaboration process with all stakeholders in the Republic of Indonesia - Malaysia border area, this increases a collaboration dynamic to many differences opinion, views, and thought patterns because there are many stakeholders which were involved in maintaining the security of the country's border area. Collaborative actions to maintain the security of the country's borders have been carried out by stakeholders, such as regular meetings, FGDs, and coordination meetings. However, these activities/events are only in such formalities, there is no serious actions in handling Republic of Indonesia - Malaysia border problems in North Kalimantan province. Therefore, the impact resulting from these collaborative activities is not significant in reducing the number of crimes between the two regencies, which directly border Malaysia, namely Malinau and Nunukan.